2023
DOI: 10.3389/fphys.2023.1137264
|View full text |Cite
|
Sign up to set email alerts
|

Field recommended concentrations of pyraclostrobin exposure disturb the development and immune response of worker bees (Apis mellifera L.) larvae and pupae

Abstract: The strobilurin fungicide pyraclostrobin is widely used to prevent and control the fungal diseases of various nectar and pollen plants. Honeybees also directly or indirectly contact this fungicide with a long-term exposure period. However, the effects of pyraclostrobin on the development and physiology of Apis mellifera larvae and pupae during continuous exposure have been rarely known. To investigate the effects of field-realistic concentrations of pyraclostrobin on honeybee survival and development, the 2-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…As long as the glucose is injected in a time-varying (periodic) manner over a proper range of frequency and amplitude, the system can be entrained into the Arnold tongues, still sustaining its oscillatory dynamics around its natural frequency. Although the role of glycolytic oscillations in physiology is not fully elucidated, glycolytic oscillations have been suggested as a pacemaker of other physiological oscillations [41][42][43]. Specifically, an oscillation of NADH, a product of glycolysis and the precursor of Kreb/electron transfer cycle, drives the oscillation of mitochondrial membrane potential [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As long as the glucose is injected in a time-varying (periodic) manner over a proper range of frequency and amplitude, the system can be entrained into the Arnold tongues, still sustaining its oscillatory dynamics around its natural frequency. Although the role of glycolytic oscillations in physiology is not fully elucidated, glycolytic oscillations have been suggested as a pacemaker of other physiological oscillations [41][42][43]. Specifically, an oscillation of NADH, a product of glycolysis and the precursor of Kreb/electron transfer cycle, drives the oscillation of mitochondrial membrane potential [44].…”
Section: Discussionmentioning
confidence: 99%
“…1B), an increased glucose injection rate beyond ν 0 ≈ 0.01 mM/s (k = 0.05 s −1 ), which could potentially be associated with the hyperglycemia, would abolish the glycolytic oscillation. Although the role of glycolytic oscillations in physiology is not fully elucidated, glycolytic oscillations have been suggested as a pacemaker of other physiological oscillations [38][39][40]. Specifically, an oscillation of NADH, a product of glycolysis and the precursor of Kreb/electron transfer cycle, drives the oscillation of mitochondrial membrane potential [41].…”
Section: Physiological Significance Of Glycolytic Oscillationsmentioning
confidence: 99%
“…Wang et al [112] reported that the gut microbiota depletion using tetracycline aggravated MPs toxicity in the A. mellifera L. This antibiotic has also been reported to cause a reduction in the digestion of pollens in honey bees [121] and elevated mortality [122]. The antimicrobials also cause gut microbiota changes and other health effects in the larvae and pupae [120,123].…”
Section: Antibioticsmentioning
confidence: 99%
“…Pyraclostrobin-contaminated beebread could induce cytotoxicity in the cells of the midgut [ 19 ]. Chronic exposure to pyraclostrobin not only altered the midgut morphology and reduced polysaccharide labeling in foragers [ 20 ], it also impaired the development, nutrient metabolism and immunity of larvae and pupae [ 21 ]. In addition, the majority of fungicides are provided as formulations, such as the commercial fungicide Pristine ® , which consists of 25.2% boscalid and 12.8% pyraclostrobin and is produced by the BASF Corporation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%